2022
DOI: 10.35833/mpce.2021.000253
|View full text |Cite
|
Sign up to set email alerts
|

Reclosing Current Limiting for DC Line Faults in VSC-HVDC Systems

Abstract: The problem of reclosing current limiting in voltage source converter based high-voltage direct current (VSC-HVDC) systems is becoming more and more serious. A soft reclosing scheme for DC permanent faults is presented in this paper. Because the converter voltages of stations at both terminals of the disconnected faulty line may be different, the choice of which terminal to reclose first will affect the reclosing overcurrent. A method for selecting the terminal to reclose first is investigated to achieve a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Various studies have highlighted the performance of HCB [22,23]. It is concluded that, as the power handling capacity of VSC-HVDC system has increased over the time, the capacity of HCB is inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have highlighted the performance of HCB [22,23]. It is concluded that, as the power handling capacity of VSC-HVDC system has increased over the time, the capacity of HCB is inadequate.…”
Section: Introductionmentioning
confidence: 99%